The Role of the Turun Tangan Lampung Community in Empowering Vulnerable Communities through Social Action - Oktavia, Destiana; Zarkasi , Ahmad; Salim, Luthfi; Fitria, Vany (Master's Program in Sociology, Faculty of Social and Political Sciences, Universitas Negeri Surabaya, 2026)
The Turun Tangan Lampung Community is a volunteer community that focuses on social activities and humanitarian actions for people in need. The Turun Tangan Lampung Community exists as a response to various social problems that have not been optimally addressed in the community, such as limited access to humanitarian assistance, minimal educational support for children, high social inequality and unequal opportunities for vulnerable communities to develop. The purpose of this study is to determine the programs run by the Turun Tangan Lampung Community and to determine the role of the Turun Tangan Lampung Community in building social awareness in vulnerable communities. This study uses a descriptive qualitative research type and uses a psychological and sociological approach. Data analysis was carried out using Max Weber's Social Action theory. The results of the study show that the Turun Tangan Lampung Community runs various programs, including Food Alms, Friday Sharing, Orphanage Assistance, Disaster Care Action, World Kaleidoscope, Milk Distribution, Book Donation, Beach Clean Up, Thousand Trees Project, Trash For Fruit. The role of the Turun Tangan Lampung community in fostering awareness among vulnerable communities includes empowerment, direct assistance, and education and literacy resources. Overall, the approach taken through these programs and roles has had a positive impact on vulnerable communities, improving their quality of life, fostering independence, and strengthening self-confidence.